1979
DOI: 10.1302/0301-620x.61b3.479262
|View full text |Cite
|
Sign up to set email alerts
|

Extra-abdominal desmoid tumours

Abstract: Desmoid tumours are not common but have a distinct resemblance to fibrosarcomata. Their clinical appearance and progress should be recognised since failure to distinguish them from sarcomata could result in extensive and unnecessarily mutilating operations. Three cases of extra-abdominal desmoid tumours are reported. Two of the patients had tumours arising from multicentric foci in the same limb. The disappearance of the tumours in two patients after the menopause, and the variation in the tumours during the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 1 publication
4
16
0
Order By: Relevance
“…However, the recommendation to treat with anti-estrogens is based on a limited number of studies reporting positive staining for ER α [2,[36][37][38][39][40][41]. In our patient collective staining for ER β was positive in only three cases, supporting data from previously conducted studies of our institution in which positive staining was found Pediatric Hematology and Oncology Pediatr Hematol Oncol Downloaded from informahealthcare.com by Gazi Univ.…”
Section: Estrogen Progesterone and Androgen Receptorssupporting
confidence: 84%
“…However, the recommendation to treat with anti-estrogens is based on a limited number of studies reporting positive staining for ER α [2,[36][37][38][39][40][41]. In our patient collective staining for ER β was positive in only three cases, supporting data from previously conducted studies of our institution in which positive staining was found Pediatric Hematology and Oncology Pediatr Hematol Oncol Downloaded from informahealthcare.com by Gazi Univ.…”
Section: Estrogen Progesterone and Androgen Receptorssupporting
confidence: 84%
“…Swelling may reappear after extensive procedures, but it is not always due to recurrence and may disappear totally or partially, as has also been noted by Enzinger and Rock. Tumours in the popliteal fossa, supraclavicular fossa, buttock, forearm and pelvis were the most difficult to cure [15]. Although tumours located in the posterior thigh and leg have a tendency to recur, wide procedures controlled all but one of our patients.…”
Section: Discussionmentioning
confidence: 74%
“…The treatment of desmoid tumors with progesterone has also been reported by several authors (Lipschutz and Grismail 1944;Nadel 1950;Dahn et al 1963;Lanari 1983). Clinically, pregnancy has been well-known to ameliorate the course of abdominal desmoid tumors (Ober et al 1955;McDougall and McGarrity 1979;Way and Culham 1999). This clinical observation has raised questions concerning the most appropriate hormonal treatment for these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone has been considered to inhibit the proliferation of desmoid tumors but further investigations are required to clarify the detailed involvement of progesterone in the biological behavior of desmoid tumors, because extra-abdominal desmoid tumors most frequently occur in the anterior abdominal wall, typically in females of childbearing age when serum progesterone levels were elevated (Musgrove and McDonald 1948;Dahn et al 1963;McDougall and McGarrity 1979;Reitamo et al 1982). In our present study, PR immunoreactivity was detected only in desmoid tumors, which suggests that PR expression is more pronounced in desmoid than in reactive fibrosis.…”
Section: Discussionmentioning
confidence: 99%